2010
DOI: 10.1080/15226510902968126
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Phytotoxicity of Heavy Metals in Remediated Soil

Abstract: Copper (Cu), zinc (Zn) and chromium (Cr) are pollutants that usually are accumulated in soils. Their toxicity can be decreased by applying amendments. We proposed to evaluate changes in Cu, Zn, and Cr availability, due to the application of amendments, through chemical analysis and phytotoxicity tests. The phytotoxicity test was carried out using species belonging to Sesbania genus; plant parameters were measured 48, 72, 96, and 168 hours after the start of incubation. The treatments included enriched soil, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…e percentage of the toxicity was found to be 11.54% indicating that the metabolites produced after degradation of battery waste are less phytotoxic when compared to the untreated sample. Similar study was performed by Branzini and Zubillaga [31] on Sesbania virgata which showed similar results but showed germination seed delay.…”
Section: Phytotoxicity Analysissupporting
confidence: 85%
“…e percentage of the toxicity was found to be 11.54% indicating that the metabolites produced after degradation of battery waste are less phytotoxic when compared to the untreated sample. Similar study was performed by Branzini and Zubillaga [31] on Sesbania virgata which showed similar results but showed germination seed delay.…”
Section: Phytotoxicity Analysissupporting
confidence: 85%
“…It is commonly accepted that the immediate impact on the environment depends on the redistribution of metals in the soil through adsorption, complexation, reduction and precipitation processes (Kunhikrishnan et al, 2013). Sequential extraction is a frequently used approach to evaluate metal redistribution into different chemical forms present in the soil, and to determine the bioavailability and ecotoxicity of heavy metals (Adriano et al, 2004;Ahmad et al, 2012a;Branzini and Zubillaga, 2010). The soluble and exchangeable forms of metals in the soil are representative of their bioavailability and toxicity to plants (Niazi et al, 2011;Ok et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples of ash addition in the composting process are observed in the literature, with the advantages of improving mineralization and humic acid formation, reducing heavy metal lability, improving process aeration and increasing macro and micronutrient content (Koivula et al 2004;Ravikumar et al 2008;Wong et al 2009;Punjwani et al 2011). Lignin % is between acceptable and high values when close to 6.48%; in this situation, the composting process could be slowed down (Branzini and Zubillaga 2010). There are several alternatives to solve this problem; among them, various microbial inoculation alternatives are mentioned (Nakasaki et al 2013;Song et al 2018).…”
Section: ₄₂₀ Ms Z�������� �� ��mentioning
confidence: 99%